Characteristics of self‑compacting green concrete - Lim, Hung Ling; Mohammad Abdul, Mannan; Rana Shamseldeen, Fakhri; Eethar Thanon, Dawood; Delsye Teo, Ching Lee; Sadia, Tasnim (Springer Nature, 2024)
Locally, conventional concrete is still created utilizing river sand and crushed stone as filer materials. The massive quarry dust by-product remain untapped in the production of concrete. The coal-fired power station produce significant quantities of Type F fly ash. Self-compacting concrete (SCC) provides many advantages for creating high-quality concrete. Consequently, the main objective of this research is to create a mix design for high-strength SCC utilizing a binary blends, hybrid fibers and fine aggregates that meet both hardened and fresh concrete characteristics. The study is conducted in amendment of w/b ratio, superplasticizer, proportion of fine aggregate to coarse aggregate, optimumal cement replacing by fly ash, dosage of low macro fibre and micro fibre. Mix-50c-X is the best mix design that was produced. The mix quantity for 1m3 concrete was 315 kg Class F fly ash, 315 kg OPC, 630 kg quarry dust, 508 kg river sand, 400 kg coarse aggregate, 0.7% superplasticizer,0.32% w/b, 0.10% macro fiber, and 0.01% micro fiber. This SCC mixture showed fresh characteristics as well as compressive strengths of more than 22 MPa and 62 MPa after 1 day and 28 days, respectively. The results of high-strength SCC demonstrated the enormous potential for the local construction, especially precast product.